2014
DOI: 10.3109/08916934.2014.929666
|View full text |Cite
|
Sign up to set email alerts
|

In vivo analysis of helper T cell responses in patients with autoimmune polyendocrinopathy – candidiasis – ectodermal dystrophy provides evidence in support of an IL-22 defect

Abstract: Autoimmune polyendocrinopathy - candidiasis - ectodermal dystrophy (APECED) is caused by mutations in the Autoimmune regulator (AIRE) gene and is associated with neutralizing anti-cytokine autoantibodies. We have used an in vivo challenge model to analyze antigen-specific CD4(+) T cell responses. Bacille Calmette-Guérin (BCG)-vaccinated patients and controls were injected tuberculin intradermally, skin blisters were induced by suction on the indurations and on unexposed skin, and the infiltrating cells harvest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…In contrast to several other syndromes associated with CMC [78,79], the circulating lymphocytes of APECED patients produce normal or even increased amounts of IL-17A [80,81], but are deficient in IL-22 and IL-17F secretion [69,80,81]. Moreover, the production of IL-22 is severely impaired by the skin-populating T cells of APECED patients [82]. APECED patients also develop high titer neutralizing autoantibodies against IL-22, IL-17F and IL-17A [29,69].…”
Section: Chronic Mucocutaneous Candidiasismentioning
confidence: 78%
“…In contrast to several other syndromes associated with CMC [78,79], the circulating lymphocytes of APECED patients produce normal or even increased amounts of IL-17A [80,81], but are deficient in IL-22 and IL-17F secretion [69,80,81]. Moreover, the production of IL-22 is severely impaired by the skin-populating T cells of APECED patients [82]. APECED patients also develop high titer neutralizing autoantibodies against IL-22, IL-17F and IL-17A [29,69].…”
Section: Chronic Mucocutaneous Candidiasismentioning
confidence: 78%
“…One study of five patients reported increased frequency of Th17 cells after stimulation with Candida [16], while another suggested a normal frequency of circulating cells co-expressing CXCR3 and CCR6, surrogate markers for IL-17A-producing cells [17]. Recently, we have studied Th17 responses in APECED patients in vivo and found a predominant defect in IL-22 production both in antigenchallenged skin and unexposed skin [18]. Similarly, the composition of the CD4 + population has been reported to be either normal or skewed, and the full pattern of functional Th differentiation has not been studied [17,19,20].…”
Section: Introductionmentioning
confidence: 94%
“…Although recipient-derived IL-22 was shown to be protective for gut tissue after allogeneic BMT, the potential benefit of IL-22 was limited during GVHD due to the elimination of recipient-derived IL-22+ ILCs by alloreactive donor T cells (137). This pathophysiology of IL-22 deficiency in GVHD may have a natural parallel in autoimmune polyendocrinopathy - candidiasis - ectodermal dystrophy (APECED) patients who have neutralizing antibodies to cytokines including IL-22, contributing to their susceptibility to candidal infections (372, 373). Furthermore, colon biopsy samples from patients with IBD have also demonstrated a deficiency of IL-22 + cells, and impaired T cell and innate cell IL-22 production has been reported in a primate model of celiac disease, indicating that intestinal pathology due to loss of IL-22-producing cells is not limited to GVHD pathogenesis and the transplant setting (374, 375).…”
Section: ) Systemic Effects Of Il-22mentioning
confidence: 99%